Potential Rice Husk Ash (RHA) For Clinker Substitute in K400 Concrete Compressive Strength Applications - Dody Guntama; Gilang Lukman Hakim; Nur Amin (Universitas Islam Sultan Agung, 2022)
Rice husk ash is a waste of rice husk combustion with pozzolanic properties and contains relatively high silica. Therefore, rice husk ash can be used as a cement substitute to manufacture concrete. This study aims to determine the performance of rice husk ash as a clinker substitute for the compressive strength of the K400 concrete produced. Rice husk ash used in this study was first ground to pass a 45 mm sieve. Then the K400 concrete mix design was made with three variations of adding rice husk ash: 0%, 10%, and 20% of the total cement consumption. The tests carried out on the test objects included slump testing and compressive strength testing for concrete aged 3, 7, 28 days. Slump flow testing is carried out to see the ease of work. At the same time, compressive strength testing is carried out to determine the quality of the concrete itself. Based on the Compressive Strength tool observing, adding rice husk ash, as much as 10% has a strength value that reached the standard compressive strength determined at 28 days. On the other hand, adding rice husk ash more than 10% produces a lower compressive strength of concrete than the standard.